Within- and Between-Session Prefrontal Cortex Response to Virtual Reality Exposure Therapy for Acrophobia - Landowska, Aleksandra; Roberts, David; Eachus, Peter; Barrett, Alan (Frontiers in Human Neuroscience, 2018)
Exposure Therapy (ET) has demonstrated its efficacy in the treatment of phobias, anxiety and PTSD, however, it suffers high drop- out rate because of to low or to high patient engagement in treatment. Virtual Reality Exposure Therapy (VRET) is comparably effective regarding symptom reduction and offers an alternative tool to facilitate engagement for avoidant participants. Neuroimaging studies have demonstrated that both exposure therapy and virtual reality exposure therapy normalise brain activity within a fear circuit. However, previous studies have employed brain imaging technology which restricts people’s movement and hides their body, surroundings and therapist from view. This is at odds with the way engagement is typically controlled. We used a novel combination of neural imaging and virtual reality technology - Functional Near-Infrared Spectroscopy (fNIRS) and Immersive Projection Technology (IPT), to avoid these limitations. Although there are a few studies that have investigated the effect of VRET on a brain function after the treatment, the present study utilised technologies which promote ecological validity to measure brain changes after VRET treatment. Furthermore, there are no studies that have measured brain activity within VRET session. In this study brain activity within the prefrontal cortex was measured during three consecutive exposure sessions. N=13 acrophobic volunteers were asked to walk on a virtual plank with a 6m drop below. Changes in oxygenated and deoxygenated hemoglobin concentrations in the prefrontal cortex were measured in three blocks using fNIRS. Consistent with previous fMRI studies, the analysis showed decreased activity in the dorsolateral and medial prefrontal cortex during first exposure. The activity increased toward normal across three sessions. The study demonstrates potential efficacy of a method for measuring within-session neural response to virtual stimuli that could be replicated within clinics and research institutes, with equipment better suited to an exposure therapy session and a fraction of the cost, when compared to fMRI. This has application in widening access to, and increasing ecological validity of, immersive neuroimaging across understanding, diagnosis, assessment, and treatment of, a range of mental disorders such as phobia, anxiety, and post-traumatic stress disorder or addictions.